Return to Work and Sport Following High Tibial Osteotomy: A Systematic Review. (21st September 2016) - Ekhtiari, Seper; Haldane, Chloe E.; de SA, Darren; Simunovic, Nicole; Musahl, Volker; Ayeni, Olufemi R.
Abstract : Background: The purpose of this study was to examine (1) timelines for return to sport and work following high tibial osteotomy (HTO), and (2) whether patients return to sport and work at levels similar to preoperative levels. Methods: A systematic search was conducted across 3 databases (MEDLINE, Embase, and PubMed). Two reviewers independently screened the results for relevant articles. Data regarding patient demographics, indications, surgical technique, return to work and sport, and complication and failure rates were abstracted from eligible studies. Results: Nineteen studies were included, involving 1, 189 patients (64% male, 21% female, 15% unspecified) and 1, 224 knees. Mean age was 46.2 years (range, 16 to 80 years). Opening-wedge HTO was most commonly used, followed by closing-wedge HTO and hemicallotasis. Mean follow-up was 65.4 months (range, 8 to 253 months). Overall, 87.2% of patients returned to sport postoperatively, and 78.6% returned at an equal or greater level. Among competitive athletes, 54% returned to competition. Overall, 84.5% of patients returned to work postoperatively, and 65.5% returned at an equal or greater level. Approximately 90% of patients who returned to work or sport did so within 1 year. The complication rate was 5.8%, with infection being the most common complication; 7.0% of patients progressed to a total knee arthroplasty at a mean of 6.7 years (range, 0.8 to 15 years) following HTO. Conclusions: The majority of patients undergoing HTO return to sport and work, and most return within 1 year of the operation. Most patients return to sport at a level equal to or greater than the preoperative level. Approximately two-thirds of patients return to an equal or greater level of physical work. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.